2023
DOI: 10.1002/glia.24354
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Rac1/PAK1/connexin43‐mediated ATP release from astrocytes contributes to retinal ganglion cell survival in experimental glaucoma

Abstract: Background: Connexin43 (Cx43) is one of major gap junction proteins in glial cells. Mutation in the gap junction protein alpha 1 gene of Cx43 has been detected in human glaucomatous retinas, suggestive of involvement of Cx43 in pathogenesis of glaucoma. However, the role of Cx43 in glaucoma has not been clearly elucidated.Methods: A mouse model of chronic ocular hypertension (COH) was produced by injecting magnetic microbeads into the eye anterior chamber. To explore the role of Rac1 in regulating Cx43 functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…The role of RhoA and actin fibers in the traffic [7][8][9][32][33][34], and function of connexins [21,[35][36][37], have been centered on GJCs. Few studies focus on HCs [26,38,41]. Here, we showed that RhoA and actin modulate the traffic of HCs to the appositional and non-appositional plasma membrane in different ways.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The role of RhoA and actin fibers in the traffic [7][8][9][32][33][34], and function of connexins [21,[35][36][37], have been centered on GJCs. Few studies focus on HCs [26,38,41]. Here, we showed that RhoA and actin modulate the traffic of HCs to the appositional and non-appositional plasma membrane in different ways.…”
Section: Discussionmentioning
confidence: 87%
“…For example, one report showed that a reduction in RhoA expression correlates with less expression of Cx26 and Cx43 in human colonic smooth muscle cells [42] or reduced connexin-mediated ATP release in lung epithelial cells [43]. In contrast, the inhibition of RhoA produced upregulation of Cx26, Cx30, and Cx43 in human nasal epithelial cells [44] and astrocytes [41]. Moreover, activation of RhoA/ROCK promote an increase of Cx43 expression in the nephron [45], suggesting that the effect of RhoA on Cx expression may be cell type specific.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining in flat retinal whole mounts was done as previously described [20]. Briefly, the eyeballs were fixed, and the retinas were isolated and blocked.…”
Section: Methodsmentioning
confidence: 99%